Профессиональный английский язык для геоэкологов ИПР электронный курс - Матвеенко, И. А. лингвист профессор Томского политехнического университета, доктор филологических наук 1967- (TPU Moodle, 2015)
В курсе "Профессиональный английский язык для геоэкологов ИПР" рассматриваются темы занятий: Introduction to Geoecology, The Impact of Oil and Coal Extraction on the Environment, Problems of Energy Production, представленные в виде 5 .юнитов Geoecology, The Impact of Mining and Oil Extraction on the Environment, Problems of Power Generation, Greenhouse Effect, The Impact of Chemical Elements on Human Organism (общей трудоемкостью 24 часа). Повторяется грамматический материал: Attribute Groups, Infinitive Constructions, Structure and word order in a sentence; Adjectives; Prepositions of place/time; Word formation.